A shift in the EU VAT system: The proposed implementation of the 'destination principle' to intra-EU B2B supplies of goods. (2nd January 2015) - Whittle, Edward
Abstract : This article provides a summary of the European Commission's report 'Implementing the destination principle to intra-EU B2B supplies of goods', produced by Ernst & Young in July 2015. The report was commissioned in order to analyse five alternative VAT taxation models for the B2B supply of goods in the EU that had been identified by the Commission as being potential solutions to two inherent problems associated with the current EU VAT system: high VAT compliance costs associated with cross-border trade for businesses, and VAT fraud levels. In this article, the key features of each of the five options are discussed, together with how they will be implemented in practice in both straight forward B2B cross-border transactions and also in relation to more complex B2B cross-border supply chains. This article provides an overview of the potential impact of each option on business VAT compliance costs, VAT fraud and the wider economy. In addition, it also considers member state tax authority administration costs, cash flow impact and reporting obligations. From the analysis carried out, it will be identified which option(s) result in the most beneficial impact from the perspective of VAT administration costs, fraud reduction, and economic impact. In addition, this article will provide some further detail as to the Commission's proposed next steps following publication of the study.